PELATIHAN OPTIMALISASI LABORATORIUM TEKNOLOGI INFORMASI DAN KOMUNIKASI (TIK) SEBAGAI PENUNJANG PROSES PEMBELAJARAN - Arif Mahya Fanny; Susi Hermin Rusminati; Rarasaning Satianingsih; Dian Kusmaharti; Bramianto Setiawan (Kanigara, 2023)
The computer laboratory functions as a place to develop skills in information and communication technology (ICT). Therefore, management of ICT laboratories is needed to assist and facilitate the learning process for teachers and students. The observation results show that most of the teachers still do not understand information and communication technology laboratories in elementary schools. Therefore, in this community service, training and assistance are provided in the management of the Information and Communication Technology Laboratory (ICT). The results of the dedication show that all respondents stated that this training was useful and very useful for managing ICT laboratories in elementary schools.